Analisis Penawaran Ubi Kayu di Kabupaten Gunung Kidul - Listiyani Listiyani (Jurnal Dinamika Sosial Ekonomi, 2001)
This research aims to identifying the factors that influence of cassava supply. The methode of research was descriptive. The data used were time series during 21 years (1977 to 1997) The estimation of growth of area, production, and productivity used semi logaritmic model, to estimate supply response used Nerlovian adjustment model. The result of the analysis show that growth of cassava production and productivity are possitive and significant, that means every year occur increase production and productivity. Cassava supply at Gunungkidul regency was not responsive to cassava price, because of the region physical condition, habits in cultivation, and social economic conditions of farmer.Keywords: cassava supply, production & productivity, cassava price.